Conjuntos ''Pérolas do Rio Branco'': o Programa Minha Casa Minha Vida no município de Boa Vista - RR - Silva, Surai Gomes da (2017)
This research is located in the field of human geography, having as its central object the seven housing Pérolas do Rio Branco built from the Programa Minha Casa, Minha Vida in the municipality of Boa Vista-RR. The study proposes to discuss some fundamental concepts for understanding housing, along with development, quality of life and territory. In this context, the main question is the public housing policies implemented through the Programa Minha Casa, Minha Vida in the municipality of Boa Vista, in the perspective of the social representation and identity of the residents in the groups. The dissertation considers the socioeconomic aspects, the dynamics of urbanization and the way individuals interact with housing. In order to contextualize the question, it presents public housing policies in the government of Getúlio Vargas, Fernando Color de Melo, Itamar Franco, as well as in the governments of Fernando Henrique Cardoso, Luís Inácio da Silva and Dilma Rousseff. The theme of housing provision is debated and highlights the attempt to cushion the demand for housing since the 1930s, with emphasis on the implementation of the National Housing Bank until its extinction. The method used was documentary research related to the public policies of the Programa Minha Casa, Minha Vida, and interview with project coordinators, on-site observation of the set and its photographic record and, finally, the use of questionnaires with a universe of 72 people distributed in the 7 housing complexes Pérolas.